Dynamic Mechanical Behavior Analysis of Flax/Jute Fiber-Reinforced Composites under Salt-Fog Spray Environment - Fiore, Vincenzo (Polymers (Basel), 2020)
Over the last decades, natural fiber-reinforced polymer composites (NFRPs) gained great attention in several engineering fields thanks to the reduction of the environmental impact and the end-of-life cost disposal. Unfortunately, the use of NFRPs is limited, mainly due to their weak resistance against humid environments. Since limited literature is available about the evolution of the dynamic mechanical response of NFRPs under aggressive environments, this paper aims to investigate the damping properties of flax, jute and flax/jute epoxy composites exposed to salt-fog up to 60 days. Furthermore, sodium bicarbonate fiber treatment was performed to improve the composites’ durability. The effectiveness of treatment was evidenced for full flax-reinforced composites, whereas no beneficial effect was found for jute composites. Moreover, treated hybrid laminates having outer laminae reinforced with flax showed better damping behavior than their hybrid counterparts during the whole aging campaign.